Kell nekünk régió? Gondolatok Tóth József pécsi geográfus örökségéről - Pap, Norbert (Modern Geográfia, 2023)
This essay is about the intellectual legacy of József Tóth, professor of geography at the University of Pécs. The main topics we have attempted to assess are regionalism in Hungary, the tasks of geography, the local, regional and international tasks of the University of Pécs, the Institute of Geography and Earth Sciences in Pécs, and the operation of the Doctoral School of Earth Sciences. The author has based his research on his personal experiences as a student and staff member, as well as on interviews and written sources. The paper presents the timeless achievements of József Tóth’s work, the training portfolio, the university integration, the development of the Faculty of Sciences, and the establishment of the Doctoral School of Earth Sciences, approaching the issue from the perspective of sustainability.